Salmon feed additive and preparation method thereof - HUANG HE; YAN LEI; LYU MINGBIN (2016)
The invention provides a salmon feed additive. The additive is prepared from chlorella, soybean oil, fructus gardenia, wild rice shoots, edible amaranth, bitter gourds, oranges, fructus forsythia, honeysuckle flowers, amomum flowers, liquorice roots, mile swertia herb, alysicarpus vaginalis, rhizoma coptidis honey and rape pollen. The salmon feed additive has the advantages that the ingredients have medicinal and edible dual effects, the immunity of salmons can be improved, and fin rot of the salmons can be effectively treated and prevented. The salmons eating the additive are high in disease resistance, high in growth speed and rich in meat nutrition, economic benefits of farmers are greatly increased, and the advantages of being simple, scientific and reasonable in formula, purely natural, environmentally friendly, free of residues, high in practicality, free of toxic and side effects and remarkable in effect are achieved. 本发明提供种三文鱼饲料添加剂，所述添加剂包括以下原料组分：小球藻、豆油、栀子、茭白、苋菜、苦瓜、柳橙、连翘、金银花、砂仁花、甘草、青叶丹、狗蚁草、黄连蜜和油菜花粉。本发明